Metabolic Profiles in Obese Children and Adolescents with Insulin Resistance - Kostovski, Marko (Open Access Maced J Med Sci, 2018)
BACKGROUND: In the past several decades, the increasing frequency of overweight and obese children and adolescents in the world has become a public health problem. It has contributed significantly to the already high tide of diabetes, cardiovascular and cerebrovascular diseases. AIM: To investigate the frequency of insulin resistance and to evaluate the metabolic profile of insulin resistant and non-insulin resistant obese children and adolescents. SUBJECTS AND METHODS: The study included 96 (45 boys, 51 girls) obese children and adolescents aged 4-17 years old (10.50 ± 2.87 years). Only participants with Body Mass Index ≥ 95 percentile were included. We analysed sera for fasting insulin levels (FI), fasting serum triglycerides (TG), total serum cholesterol (TC), fasting plasma glucose (FPG) and plasma glucose 2 hours after the performance of the oral glucose tolerance test (2-h G). Homeostatic model assessment for insulin resistance (HOMA-IR) index was calculated as fasting insulin concentration (microunits per millilitre) x fasting glucose concentration (millimolar)/22.5. The value of HOMA-IR above 3.16 was used as a cut-off value for both genders. RESULTS: Insulin resistance was determined in 58.33% of study participants. Insulin resistant participants had significantly higher level of 2-h G (p = 0.02), FI level (p = 0.000) as well as TG levels (p = 0.01), compared to non-insulin resistant group. Strikingly, 70.73% of the pubertal adolescents were insulin resistant in comparison to 49.09% of the preadolescents (p = 0.03). Significantly higher percentage of insulin-resistant participants were girls (p = 0.009). Moreover, a higher percentage of the girls (70.59%) than boys (44.44%) had HOMA-IR above 3.16 and had elevated FI levels (70.59% vs 48.89%). The difference in the frequency of insulin resistance among obese versus severely obese children and adolescents was not significant (p = 0.73, p > 0.05). Our study results also showed positive, but weak, correlation of HOMA-IR with age, FPG, TG and BMI of the participants (p < 0.05). CONCLUSION: Higher percentage of insulin-resistant participants was of female gender and was adolescents. In general, insulin resistant obese children and adolescents tend to have a worse metabolic profile in comparison to individuals without insulin resistance. It is of note that the highest insulin resistance was also linked with the highest concentrations of triglycerides.